ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUASAN PELANGGAN (Studi Kasus pada Home Industri Kaca Grafir di Desa Grujugan Kidul Kecamatan Grujugan Bondowoso) - Damanhuri Damanhuri; Muhammad Firdaus; Yani Dahliani (STIE Mandala Jember, 2013)
Companies need to understand the things that is closely related to customer satisfaction: quality of product, quality of service, and price. Based on this, the aim of this study were to analyze the effect of product quality, service quality, and price to customer satisfaction in the Home Industrial Glass Engraving in the Grujugan Kidul Village, Grujugan District Bondowoso Regency. This study are used primary data and multiple regression analysis. The results showed that the variable quality of the product and prices significantly affect customer satisfaction. Most of customer satisfaction in the Home Industrial Glass Engraving are influenced by the quality of the product and the price.